Restoration of CTSD (cathepsin D) and lysosomal function in stroke is neuroprotective. Issue 6 (3rd June 2021) - Hossain, M. Iqbal; Marcus, Joshua M.; Lee, Jun Hee; Garcia, Patrick L.; Singh, VinodKumar; Shacka, John J.; Zhang, Jianhua; Gropen, Toby I.; Falany, Charles N.; Andrabi, Shaida A.
ABSTRACT: Stroke is a leading cause of death and disability. The pathophysiological mechanisms associated with stroke are very complex and not fully understood. Lysosomal function has a vital physiological function in the maintenance of cellular homeostasis. In neurons, CTSD (cathepsin D) is an essential protease involved in the regulation of proteolytic activity of the lysosomes. Loss of CTSD leads to lysosomal dysfunction and accumulation of different cellular proteins implicated in neurodegenerative diseases. In cerebral ischemia, the role of CTSD and lysosomal function is not clearly defined. We used oxygen-glucose deprivation (OGD) in mouse cortical neurons and the middle cerebral artery occlusion (MCAO) model of stroke to assess the role of CTSD in stroke pathophysiology. Our results show a time-dependent decrease in CTSD protein levels and activity in the mouse brain after stroke and neurons following OGD, with concurrent defects in lysosomal function. We found that shRNA-mediated knockdown of CTSD in neurons is sufficient to cause lysosomal dysfunction. CTSD knockdown further aggravates lysosomal dysfunction and cell death in OGD-exposed neurons. Restoration of CTSD protein levels via lentiviral transduction increases CTSD activity in neurons and, thus, renders resistance to OGD-mediated defects in lysosomal function and cell death. This study indicates that CTSD-dependent lysosomal function is critical for maintaining neuronal survival in cerebral ischemia; thus, strategies focused on maintaining CTSD function in neurons are potentially novel therapeutic approaches to prevent neuronal death in stroke. Abbreviations: 3-MA: 3-methyladenine; ACTB: actin beta; AD: Alzheimer disease; ALS: amyotrophic lateral sclerosis; CQ: chloroquine; CTSB: cathepsin B; CTSD: cathepsin D; CTSL: cathepsin L; FTD: frontotemporal dementia, HD: Huntington disease; LAMP1: lysosomal associated membrane protein 1; LSD: lysosomal storage disease; MCAO: middle cerebral artery occlusion; OGD: oxygen glucose deprivation; OGR: oxygen glucose resupply; PD: Parkinson disease; SQSMT1: sequestosome 1; TCA: trichloroacetic acid; TTC: triphenyl tetrazolium chloride.